KOORDINASI PENGAWAS DAN KEPALA SEKOLAH DALAM SUPERVISI AKADEMIK UNTUK MENINGKATKAN KOMPETENSI PROFESIONAL GURU DI WILAYAH GUGUS 1 KOTA BAKTI KABUPATEN PIDIE - Nurbaiti .; Yusrizal .; Niswanto . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2019)
Coordination between supervisor and principal is a necessity in performing a supervision. This study aimed at finding out: academic supervision programs and the obstacles faced in performing supervision to all teachers to develop teachers’ professionalism competence. This study employed descriptive method with qualitative approach. The data in this study were obtained from observation, interview, and documentation. The subjects of this study were supervisors, principals, and teachers. The results showed that: (1) The supervision program to develop teacher’s professionalism for elementary level had been arranged and documented in the form of annual and semester programs. Supervisors had performed supervision works, counseling,  guidance,  and  direct  teachers  to  help   them develop their teaching competence; (2) This supervision was done through class guidance, class observation, unplanned test, case conference, documentation, interview, questionnaire, and printed report; (3) In responding supervision results, the supervisors applied educative and persuasive manner to help teachers who face difficulties in developing their teaching competence by providing discussion, case conference, and question session between supervisors; and (4) distance and wide area were obstacles faced by supervisors to visit each of school. Keywords: Supervisors’ Coordination, Principal, and Academic Supervision